SHUKUR KOLMIRZAYEV'S WAY OF LIFE (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article is about the life and work of Shukur Kholmirzayevabout information, works, stories, about the study of his work in literaturewill be considered.